Residues of selected sulfonamides, non-steroidal anti-inflammatory drugs and analgesics-antipyretics in surface water of the Elbe river basin (Czech Republic) - Skocovska, Marie; Ferencik, Martin; Svoboda, Martin; Zdenka, Svobodova (Veterinarni medicina, 2021)
The occurrence of human as well as veterinary drug residues in surface water is caused by their insufficient removal ability from wastewater. Drug residues disturb the natural balance of water ecosystem, have a negative effect on non-target organisms and pose a significant risk for human health. The main aim of this study was to determine the concentration of residues of eight drugs from the group of sulfonamides (sulfathiazole, sulfadiazine, sulfamethazine, sulfamethoxazole, sulfadimethoxine, sulfadoxine, sulfamerazine, sulfachlorpyridazine), four drugs from the non-steroidal anti-inflammatory drug group (ibuprofen, ketoprofen, naproxen, diclofenac) and one representative of the analgesics-antipyretics group [paracetamol (acetaminophen)] in the surface water of the Elbe river basin. A total of 65 samples of surface water from the Elbe river basin were taken during August 2018 when the weather was constant without any significant fluctuations. The analysis was performed by means of liquid chromatography with tandem mass spectrometry (LC-MS/MS). The results have shown the numerous occurrences of sulfamethoxazole, ibuprofen, naproxen, diclofenac and paracetamol (acetaminophen). A statistically significant negative correlation between the river flow rate in the monitored locations and the residue concentration was found for ibuprofen, naproxen, diclofenac and paracetamol (acetaminophen). The most significant findings of the monitored drug residues were mostly determined in samples from small streams below larger urban settlements with a hospital or other health facilities.
Keywords: paracetamol (acetaminophen); naproxen; diclofenac; ibuprofen; sulfamethoxazole